2022
DOI: 10.1021/acsnano.1c10838
|View full text |Cite
|
Sign up to set email alerts
|

From 2D to 3D: Postsynthetic Pillar Insertion in Electrically Conductive MOF

Abstract: The emergence of 2D electrically conductive metal–organic frameworks (MOFs) has significantly expanded the scope of metal–organic framework applications from electrochemical energy storage to electronic devices. However, their potentials are not fully exploited due to limited accessibility to internal pores in stacked 2D structures. Herein we transform a 2D conjugated MOF into a 3D framework via postsynthetic pillar-ligand insertion. Cu-THQ was chosen due to its ability to adopt additional ligands at the axial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 25 publications
0
38
0
2
Order By: Relevance
“…As the water reduction potential lies at 0 V vs NHE, so it can be concluded that photogenerated electrons of Ni-SIP-BPY with a more negative potential (−0.37 V vs NHE) may have ability to reduce the water and are capable of H 2 generation. Furthermore, we have also calculated the electrochemically active surface area (ECSA) through electrochemical double-layer capacitance measurement ( C dl ) . The electrochemical double-layer capacitance was evaluated by measuring cyclic voltammetry (CV) data in the non-Faradic region at different scan rates from 20 to 200 mV/s (Figure S19b) in 0.1 M Na 2 SO 4 medium, and the observed value was 0.026 mF cm –2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the water reduction potential lies at 0 V vs NHE, so it can be concluded that photogenerated electrons of Ni-SIP-BPY with a more negative potential (−0.37 V vs NHE) may have ability to reduce the water and are capable of H 2 generation. Furthermore, we have also calculated the electrochemically active surface area (ECSA) through electrochemical double-layer capacitance measurement ( C dl ) . The electrochemical double-layer capacitance was evaluated by measuring cyclic voltammetry (CV) data in the non-Faradic region at different scan rates from 20 to 200 mV/s (Figure S19b) in 0.1 M Na 2 SO 4 medium, and the observed value was 0.026 mF cm –2 .…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we have also calculated the electrochemically active surface area (ECSA) through electrochemical doublelayer capacitance measurement (C dl ). 66 The electrochemical double-layer capacitance was evaluated by measuring cyclic voltammetry (CV) data in the non-Faradic region at different scan rates from 20 to 200 mV/s (Figure S19b) in 0.1 M Na 2 SO 4 medium, and the observed value was 0.026 mF cm −2 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…22,23 For example, researchers found that a nonporous interpenetrated framework, Zn(cyanide) 2 , underwent lattice distortion at the high pressure of 1.50−1.58 GPa, and transformed into noninterpenetrated porous phases with three different kinds of topologies in pressure-transmitting fluids. 21 Another example highlighted a transformation from two-dimensional (2D) MOFs to three-dimensional (3D) frameworks by pillar insertion, 24 corresponding to an increment of surface area with structural augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…Lattice transition commonly includes (1) breathing triggered by guest molecules, that is, lattice switching between the large pore and narrow pore; (2) structural distortion as a result of linker rotation and reorientation; , (3) lattice contracting/expanding via external stimuli such as temperature; , and (4) complete topological transformation with respect to the reorganization of secondary building units driven by the cleavage and reconstruction of metal-linker chemical bonds. , For example, researchers found that a nonporous interpenetrated framework, Zn­(cyanide) 2 , underwent lattice distortion at the high pressure of 1.50–1.58 GPa, and transformed into non-interpenetrated porous phases with three different kinds of topologies in pressure-transmitting fluids . Another example highlighted a transformation from two-dimensional (2D) MOFs to three-dimensional (3D) frameworks by pillar insertion, corresponding to an increment of surface area with structural augmentation.…”
Section: Introductionmentioning
confidence: 99%
“…benzene and triphenylene) are optimal because the coordination tends to form strong inplane conjugation and π-π stacking. 17,18 This in-plane conjugated effect possesses the ability to interact with out-of-plane van der Waals, which promotes the intrinsic charge transport of 2D MOF layers. 19,20 Such a strong interaction caused by electron coupling at a large plane greatly restricts the exfoliation of 2D MOF-derived carbon sheet layer, resulting in inadequate exposure of active sites.…”
Section: Introductionmentioning
confidence: 99%